Staining criteria, collection and number of cells evaluated to identify micronuclei in buccal mucosa cells of agricultural workers exposed to pesticides. - Santiago-Manzano , Dayna (Mexican Journal of Medical Research ICSA, 2021)
Although there are several publications that refer to the basic criteria established for the micronucleus (MN) test in exfoliated buccal cells, there is still a difference in the quantity, method of obtention and staining of the cells for the evaluation of the presence of micronuclei. Objective. Identify the criteria for evaluation of MN in oral mucosa cells exposed to pesticide in investigations carried out. Material and methods. A systematic review was carried out on the internet, based on articles published in Crossref, JCR, Scopus, PubMed, Google academic, using keywords such as: micronuclei, buccal mucosa cells, genotoxic damage, pesticides and biomarker. Results. In the six selected articles, four presented statistically significant values ​​with the presence of MN when comparing the exposed groups with respect to the control groups, and the criteria for staining, collection and number of cells evaluated to identify micronuclei were very varied. Conclusions. It is important to follow validated and standardized protocols for the MN oral cytoma assay. Being considered in all the parameters suggested in the protocol will increase the reliability of the studies and will give the possibility of comparing the results obtained.